Accreditation of Quality in Primary Health Care in Chile: Perception of the Teams from Accredited Family Healthcare Centers - Rojas-Pavez, J; Coss-Mandiola, J; Vanegas-Lopez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This study aimed to investigate the perception of the health teams belonging to the Family Healthcare Centers (CESFAMs) that are accredited, regarding the process of implementation and the achievement of accreditation. A qualitative approach was applied, with contributions from grounded theory, through the technique of individual in-depth interviews and focus groups. The interviews were carried out in nine accredited CESFAMs. For the presentation, organization and analysis of the data, Atlas.ti V9 software was used. From the results, derived from the open phase of the analysis, obtained from the opinions of the participants, a total of 26 categories emerged relating to the facilitating and hindering factors of the process. From the axial phase, it was possible to establish central categories that were related to quality management policies, the structure of Primary Health Care (PHC), participation and co-construction, and leadership and change management. In conclusion, the discourse of the teams reveals the need to have necessary conditions for the accreditation process, which are mainly related to training, characteristics of the types of leadership and teamwork in harmony with the process. Finally, the study reveals a gap in the community participation in this process, which suggests continuing this line of research. © 2023 by the authors.